The Role of Palliative Care in Chronic Progressive Neurological Diseases—A Survey Amongst Neurologists in the Netherlands - Walter, Hannah A. W.; Seeber, Antje A.; Willems, Dick L.; de Visser, Marianne (Frontiers in Neurology, 2019)
Background Chronic progressive neurological diseases like high grade glioma (HGG), Parkinson’s disease (PD) and multiple sclerosis (MS) are incurable, and associated with increasing disability including cognitive impairment, and reduced life expectancy. Patients with these diseases have complex care needs. Therefore, timely advance care planning (ACP) is required. Our aim was to investigate timing and content of discussions on treatment restrictions, i.e. to initiate, withhold or withdraw treatment in patients with HGG, PD and MS, from the neurologists’ perspective. Methods We performed a national online survey amongst consultants in neurology and residents in The Netherlands. The questionnaire focused on their daily practice concerning timing and content of discussions on treatment restrictions with patients suffering from PD, MS or HGG. We also inquired about education and training in discussing these issues. Results A total of 125 respondents (89 neurologists (71%), 62% male, with a median age of 44 years and 36 residents (29%), 31% male with a median age of 29 years) responded. Initial discussions on treatment restrictions were said to take place during the first year after diagnosis in 28% of patients with HGG, and commonly no earlier than in the terminal phase in patients with PD and MS. In all conditions, significant cognitive decline was the most important trigger to advance discussions, followed by physical decline and initiation of the terminal phase. Most discussed issues included ventilation, resuscitation, and admission to the intensive care unit. More than half of the consultants in neurology and residents felt that they needed (more) education and training in having discussions on treatment restrictions. Conclusion In patients with HGG discussions on treatment restrictions are initiated earlier than in patients with PD, MS. However, in all three diseases these discussions usually take place when significant physical and cognitive decline has become apparent and commonly mark the initiation of end-of-life care. More than half of the responding consultants in neurology and residents feel the need for improvement of their skills in performing these discussions.